'A whole new world opened up': the impact of place and space-based professional development on one rural South Africa primary school. Issue 5 (20th October 2019) - Flint, Amy Seely; Albers, Peggy; Matthews, Mona
ABSTRACT: Project Partnerships Achieve Literacy (PAL) South Africa was designed to transform teachers' pedagogical practices in literacy instruction in an under-resourced school and, by doing so, improve the reading achievement of foundation phase students (Grades R–3). Sociocultural and situative theories of literacy and learning frame the study. To gauge effectiveness of the Project, we undertook a two-year study to examine changes in learners' literacy growth and teachers' conceptual and pedagogical knowledge of literacy development as a result of the teachers' participation in the Project. Given the dual aims of this study, we applied a qualitative dominant mixed methods design. Data analysis revealed three major findings: (1) teachers' literacy practices shifted toward a more generative and culturally responsive approach ; (2) children's literacy skills were positively impacted by teachers' increased literacy pedagogical practices and knowledge; and (3) three characteristics of professional emerged that impacted teachers' practices. Results indicate that for transformation in pedagogy and ultimately in learners' literacy achievement, professional development must be placed and spaced, viewed as a process, and valued in a sphere of multiplicity in which social relations and real material practices are ongoing.